2021
DOI: 10.1021/acs.cgd.1c00458
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Cocrystals from Solid Solutions in Benzoic Acid–Mono/poly-fluorobenzoic Acid Combinations

Abstract: Benzoic acid–monofluorobenzoic acid combinations are known to form solid solutions, whereas benzoic acid–pentafluorobenzoic acid system forms a cocrystal. To decipher the gradation from solid solution to cocrystal between these extremes, we executed the cocrystallization of benzoic acid with several of its poly-fluoro (di-, tri-, and tetra-) substituents. The fluorine atom, with its sheer geometric position and intermolecular (hydrogen and halogen) bonding ability, is found to steer the transformation from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…In effect, complex multicomponent supramolecular systems designed through an understanding and control of synthon hierarchy will be possible. Fluorinated coformers and excipients may emerge as a new class of pharmaceutical additives. “Designed efficacious drugs” and “compact pharmaceutical manufacturing” are expected to replace the current paradigm in the drug industry.…”
Section: Discussionmentioning
confidence: 99%
“…In effect, complex multicomponent supramolecular systems designed through an understanding and control of synthon hierarchy will be possible. Fluorinated coformers and excipients may emerge as a new class of pharmaceutical additives. “Designed efficacious drugs” and “compact pharmaceutical manufacturing” are expected to replace the current paradigm in the drug industry.…”
Section: Discussionmentioning
confidence: 99%
“…Current understanding of principles governing the mixed crystallization of organic and inorganic compounds is based largely on work carried out decades ago by Kitaigorodsky and co-workers, which has not been subjected to extensive reexamination. , These pioneering studies suggested that a series of mixed crystals with continuously variable compositions in all proportions can only be obtained when the components are similar enough to crystallize isostructurally . However, more recent work has challenged this notion and shown that mixed crystals with a wide range of compositions can be formed from pairs that are not known to have a close crystallographic relationship. These recent advances, which include the discovery that mixed crystals can be effective seeds for inducing crystallization of the individual components, have made mixed crystallization an exciting area of research.…”
Section: Introductionmentioning
confidence: 99%
“…Frontera, Bokach, Kukushkin, and co-workers studied the association of (nitrosoguanidinate)­Ni­(II) with various iodine-containing halogen bond donors to examine asymmetric three-center bifurcating halogen bonds (BXBs) and hence compare the abilities of two distinct nucleophilic centers (N and O) to form XB with the donor center . Row and co-workers undertook a systematic cocrystallization study of a series of combinations of benzoic acid with several di-, tri-, and tetrafluorosubstituted benzoic acids to analyze the structural modifications of solid solutions and consequent generation of cocrystals . Type I and type II halogen bonds via para-substituted fluorine atoms in benzoic acid and other structure-directing heteromolecular interactions involving fluorine enabled the evolution of cocrystals from solid solutions.…”
mentioning
confidence: 99%
“…8 Row and co-workers undertook a systematic cocrystallization study of a series of combinations of benzoic acid with several di-, tri-, and tetrafluorosubstituted benzoic acids to analyze the structural modifications of solid solutions and consequent generation of cocrystals. 9 Type I and type II halogen bonds via para-substituted fluorine atoms in benzoic acid and other structure-directing heteromolecular interactions involving fluorine enabled the evolution of cocrystals from solid solutions. Taylor, Zhang, and co-workers reported, for the first time, halogen bonding interactions between drug molecules containing Cl, Br, or I and polymers, such as PVPVA and PVP.…”
mentioning
confidence: 99%